THE PATHS OF INTIMACY BETWEEN THE SPOUSES - FROM THE PERSPECTIVE OF THE HOLY QUR’AN (Islamic Sciences Journal, 2023)
Praise be to Allah, and may blessings and peace be upon the Messenger of Allah, his family and companions, and who is guided by him and after:The research provides effective solutions for the most prominent family problems according to the divine approach to family formation, and the coexistence of its members is based on affection and compassion.   It showed the meaning of the determinants of the address, and the extent of the Holy Qur’an taking care of the familyAnd it clarified the Qur’anic method in drawing ways to achieve intimacy between the spouses, and it included achieving the stewardship of the man, and achieving homosexuality between the spouses and cohabitation with good, and the research took care of the statement of the Holy Qur’an’s keenness to find family coexistence in light of serenity, affection, and mercy, hitting in the applied examples, relying on the applied What was received from the evidence, and the conclusion: I mentioned the most important findings.God bless our Prophet Muhammad and his  family and companions.